A transit passenger with unilateral leg pain - Ghazala Faheem (21842918) (2025)
A 57‐year‐old male transit passenger from an 8‐hour flight presented to the emergency department with severe left posterior thigh pain. He had experienced a traumatic event a few weeks prior, resulting in fractures of the left hip and left lower ribs. Upon examination, he exhibited severe tenderness, warmth, and fluctuation in the left posterior thigh with minimal swelling. He had a low‐grade fever (37.8°C), was markedly tachycardic (heart rate: 125 beats/min), and appeared clinically dehydrated. Blood investigations revealed raised inflammatory markers, elevated creatinine, and high lactate levels (Table 1). Given his clinical presentation and recent surgery combined with the long flight, initial differential diagnoses included deep venous thrombosis (DVT) and sepsis. Point‐of‐care ultrasound (POCUS) ruled out DVT but revealed subcutaneous edema with fluid collection in the hamstring muscles. Other Information Published in: JACEP Open License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/emp2.13221